RECURSOS EDUCATIVOS DIGITALES: PROCESOS DE MEDIACIÓN Y MEDIATIZACIÓN EN LA COMUNICACIÓN PEDAGÓGICA - Sulmont Haak, Lea (2005)
The knowledge processes have been experiencing radical transformations due to the latest information and communication technologies incorporation. In this stage, it is important to pay special attention to the way contents and resources productions evolves and its integration in the learning-education process. At the moment, production dynamics of the educative resources are registered by the concept of learning objects, the logical of reusability and the use of standards on the digital contents processes. These concepts suggest a new philosophy, a new way to produce contents, but above all, a new way to distribute and share them. Along to this tendency, it is necessary to look in depth aspects of pedagogical design and cognitive considerations about contents and ways in which digital resources are used as a strategy that will lead to an effective use of these elements in the learning education process. From pedagogical communication perspective, the task establishes a reflection on the interchange processes produced within the pedagogical triangle and with the contribution of technological tools and digital educative resources. The bases that support this reflection turn around the forms of mediation of the pedagogical relation and to insert content into the media through digital educative resources that use multimedia language.